2021
DOI: 10.28991/cej-2021-03091632
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Traffic Flow Characterization for Stimuli Based on Driver Reaction

Abstract: The design and management of infrastructure is a significant challenge for traffic engineers and planners. Accurate traffic characterization is necessary for effective infrastructure utilization. Thus, models are required that can characterize a variety of conditions and can be employed for homogeneous, heterogeneous, equilibrium and non-equilibrium traffic. The Lighthill-Whitham-Richards (LWR) model is widely used because of its simplicity. This model characterizes traffic behavior with small changes over a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The spatial and temporal characterization of traffic should be based on parameters such as driver response [2,5]. Real observations have been used to determine driver response to traffic conditions [25].…”
Section: Traffic Flow Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial and temporal characterization of traffic should be based on parameters such as driver response [2,5]. Real observations have been used to determine driver response to traffic conditions [25].…”
Section: Traffic Flow Modelsmentioning
confidence: 99%
“…The macroscopic model created by Lighthill, Whitham and Richards (LWR) is based on small changes in density which are characterized by variations in traffic velocity [4]. This simple model is commonly employed for traffic modeling [1,5], but it ignores traffic alignment at transitions as well as driver response. Further, the traffic flow is symmetric when the capacity is 0.5 which is not realistic [6], and driver time to adjust to changes in traffic is ignored [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the performance of the model is evaluated numerically. These results are used to modify the model as required to obtain an acceptable traffic characterization [18]. The LWR and proposed traffic models are presented below.…”
Section: Traffic Flow Modelsmentioning
confidence: 99%
“…Further, the velocity during alignment to forward conditions should be included [17]. Driver reaction has been considered to provide more realistic behavior than existing models [18,19]. Further, realistic parameters were used to better characterize traffic [20].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of road users' situation awareness in different road environments such as wet, slippery, debris, quiet and busy roads found that it can influence driver's awareness (Salmon et al, 2014). In addition, Imran et al (2021) observed that traffic flow characterization and driver reaction were related. Another opinion stated that a tired or fatigue driver has its potential to ignore traffic rules (Ho et al, 2015;Ho & Widaningrum, 2016).…”
Section: Introductionmentioning
confidence: 99%